STRENGTHENING OF INDONESIAN ISLAMIC CHARACTER THOUGH ISLAMIC EDUCATION MANAGEMENT BASED OF SOFT SKILLS - Utaminingsih, Sri; Utomo, Slamet; Zamroni, Edris (LPPM IAIN Kudus, 2017)
Symptoms of intolerance that was done by most of the ummah of Islam in Indonesia lately, shows that globalization has brought the ideology of the new that actually erode the identity of Islam Indonesia were very accommodating and tolerant of the wealth of local culture, upholding the values of diversity and emancipatory on the role of women in everyday life. Islamic educational institutions should play a role in the reconstruction of intolerance symptoms that Appeared lately. Through management soft skills-based Islamic education is expected to restore Islam Indonesia on Islam very famous identity steeped in local culture and uphold the values of diversity. This article reviews how the management arrangement soft skills-based Islamic education is Able to restore Islam Indonesia returned to his identity.